A study on the correlation between the inter-alar width and the intercanine distance - Alto, Arminda A.; Reyes, Maria Victoria S.; Ladao, Joaquin D. (Adviser).
An essential factor in attaining esthetics in complete prosthodontics is the selection of maxillary anterior teeth that have approximately the same size as their natural predecessors. While it is true that quite a number of different methods have been used, none of them has been found to be the most reliable particularly for Filipino patients. To find out if there is an existing correlation between the inter-alar width and the intercanine distance, and to determine whether the inter-alar width may be used as a clinical guide in establishing the position of the maxillary canines, a study was conducted on fifty (50) Filipino subjects using purposive sampling method. The inter-alar width and the intercanine distance were measured four times using a vernier caliper and statistical analysis was done based on average measurements. With the computed correlation coefficient (r) equal to 0.5246, it was found that a moderate positive correlation exists between the inter-alar width and the intercanine distance among the fifty subjects.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dentistry -- Aesthetic aspects; Prosthodontics